2009
DOI: 10.1111/j.1469-8986.2009.00874.x
|View full text |Cite
|
Sign up to set email alerts
|

Visuo‐spatial processing and the N1 component of the ERP

Abstract: Asymmetries in posterior ERP components, such as the N1, are generally taken to reflect the visual processing of spatial information in absolute (fixation-based) coordinates. Yet, it is also well established that the position of an object can be coded relative to the position of other objects. To examine the ERP correlates of relative spatial coding, two experiments were conducted in which spatially neutral target stimuli were preceded, accompanied, or followed by laterally presented, task-irrelevant accessory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
54
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 51 publications
9
54
2
1
Order By: Relevance
“…In line with this interpretation, there is evidence that at least the visual N1 is not a purely sensory component, but depends also on early attentional processes (Hillyard et al, 1973;Wascher and Beste, 2010;Wascher et al, 2009;Schneider et al, 2012;for reviews, Luck et al, 2000;Eimer, 2014). Within a theoretical framework of an early selection model of attention, the increase in N1 amplitude and decrease in N1 latency could reflect a sensory gating mechanism of attention, which facilitates the further processing of this rare stimulus.…”
Section: P1 and N1mentioning
confidence: 77%
See 1 more Smart Citation
“…In line with this interpretation, there is evidence that at least the visual N1 is not a purely sensory component, but depends also on early attentional processes (Hillyard et al, 1973;Wascher and Beste, 2010;Wascher et al, 2009;Schneider et al, 2012;for reviews, Luck et al, 2000;Eimer, 2014). Within a theoretical framework of an early selection model of attention, the increase in N1 amplitude and decrease in N1 latency could reflect a sensory gating mechanism of attention, which facilitates the further processing of this rare stimulus.…”
Section: P1 and N1mentioning
confidence: 77%
“…Correlates of early stimulus processing are given by the P1 and N1 deflections. While these components were initially regarded as stimulus-driven and reflecting the automatic processing of sensory input, there is evidence that top-down triggered processes of goaloriented and top-down allocation of attention affect even the early stimulus processing reflected by P1 and N1 (e.g., Schneider et al, 2012;Wascher and Beste, 2010;Wascher et al, 2009;for review, Eimer (2014)). Correlates of subsequent processing are given by the P2, N2, and N400 deflections.…”
Section: Introductionmentioning
confidence: 99%
“…When two visual stimuli are presented, one in each visual¯eld, the N170 is bilateral. In the latter case, the N170's asymmetrical skewedness is modulated by attention (Wascher et al, 2009). Additionally, its amplitude is in°uenced by selective attention, and thus it has been used to study a variety of attentional processes (Wascher et al, 2009;Luck et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The N1 reflects a later stage of visual processing that is sensitive to object categorization, unlike the P1 (e.g., Bentin et al, 1996). Furthermore, a recent study demonstrated that the hemispheric asymmetry of the N1 can reflect the relative rather than the retinotopic position of objects (Wascher et al, 2009). Thus, the P1 may be a better component with which to estimate IHTT than the N1.…”
Section: Discussionmentioning
confidence: 99%